Estudo da organização molecular em filmes de ftalocianina e bisftalocianina de gadolínio antes e após annealing - Bissani, Bruna (2021)
The study of the controlled growth of thin films has aroused considerable interest for a wide range of applications, mainly in the field of electronic devices. Molecules that can lead to optimization of electronic and optical properties when arranged in the form of thin films have been studied, as is the case of metallic phthalocyanines. As they are planar macrocyclic compounds, they have high thermal and chemical stability, and still have an intense green or blue color. Thin films fall into the category of two-dimensional materials, and can be obtained by several techniques already widespread in the literature. However, phthalocyanines have low solubility in organic solvents and water, if not substituted on the rings. A previous study of the solubility of the compounds used in this work, gadolinium phthalocyanine in mono (GdPc) and bis (GdPc2) forms, in different solvents: dimethylformamide (DMF), dimethylsulfoxide (DMSO), tetrahydrofuran (THF), chloroform ( CHCl3) and acetone. For deposition of the films of both compounds, prepared on glass and glass substrates covered with fluorine-doped tin oxide (FTO), the airbrush technique was used. The solvents for the preparation of the solutions were those where the phthalocyanines showed better solubility, DMF and CHCl3 for GdPc, and DMF and acetone for GdPc2. The films were deposited on zinc selenide substrate using DMSO for characterization by Fourier transform infrared (FTIR) spectroscopy, showing the different forms of GdPc (mono and bis). Phthalocyanine solutions in the solvents DMF, DMSO, THF, CHCl3 and acetone were characterized by absorption spectroscopy in the ultravioletvisible region (UV-Vis), showing the influence of the solvent on the characteristic bands of phthalocyanines, B and Q. characteristics of these bands indicate different arrangements of molecules, forms called  and , and presented different arrangements for the solvents used. The formed films were analyzed before and after annealing to verify the morphology and the possible changes that occurred with the annealing, such as alteration from the  phase to the  phase. These analyzes were performed by UV-Vis., X-ray diffraction (XRD) and atomic force microscopy (AFM). After annealing, the observed changes suggest a rearrangement of molecules to GdPc2 in acetone when the substrate is glass. The XRD results do not show a significant change in the FTO substrate, only in glass, suggesting that there was a reorganization of molecules on the substrate with a change from α to  phase. The morphology observed by AFM confirms this transformation in relation to the change in crystallite shape and size. The other films possibly did not complete this phase change due to lack of material deposited on the substrates.